A study on factors which affecting employee’s job satisfaction at RISDA, Jalan Khalidi, Muar, Johor / Rozina Ab Aziz - Ab Aziz, Rozina (2010)
Job Satisfaction can be as an important indicator of how employees feel about their jobs and a predictor of work behaviors. The happier people are within their job, the more satisfied they are said to be. Job satisfaction also plays an important role in defining employee’s efficiency and performance. Low job satisfaction will lead to the low morale which will cause employees to work less and concentrate more on negative aspect such as stress, depresses, absenteeism and so on. The past researcher shows that there are many factors that affect the employee’s job satisfaction. Present research study on three factors that could be the tools that can satisfy employees which are work condition, pay, and fairness. This study has been conducted within RISDA and it involved 44 respondents in different department. Results of the present study showed that the most influential factors that affects employee’s job satisfaction is work condition. It’s also shows that work condition has a positive and moderate correlation relationship with employee’s job satisfaction. Recommendations for future research are also having been discussed.